ПСИХОЛОГІЧНІ УСТАНОВКИ, КОМПЕТЕНЦІЇ ТА ОСОБИСТІ ЯКОСТІ ВИКЛАДАЧА ЯК ФАКТОР РОЗВИТКУ МАТЕМАТИЧНОЇ ОБДАРОВАНОСТІ УЧНЯ - Бончук Н. В. (International Journal of Innovative Technologies in Social Science, 2020)
The article deals with the problem of the role of professional competences, personal characteristics and psychological attitudes of the subject-teacher in the development of mathematical giftedness of students. The substantiation of the competence model of a teacher working with mathematically gifted children is presented. The urgency of the problem of formation of necessary competences for work with mathematically gifted students is substantiated. The three-level model of teacher's professional competence is considered as a set of key professional (reflecting the specificity of a certain professional activity, in our case - pedagogical) and special (reflecting the specificity of working in different conditions of professional activity with talented children) competencies.Within the competency model, the components of the cognitive, behavioral, and value components are examined. The role of the psychological ettitudes of the teacher in the motivational component of the educational process is substantiated. A number of problems of professional and personal development of teachers in the organization of teaching of mathematically gifted students have been identified. Recommendations are given for the construction of a postgraduate teacher education program aimed at the discovery and psychological and pedagogical support of mathematical talent.